Reflections on Pragmatism as a Philosophy of Architecture - David Macarthur (Footprint)
Two recent collections on architectural theory and practice invoke the name of pragmatism as marking the hope of a new more intimate alignment of theory and practice after a period of what I call ‘philosophical vampirism’.  This paper examines what role the philosophical tradition of pragmatism might play in relation to architecture. I argue that pragmatism is best understood as a method of overcoming intellectualist and metaphysical obstacles to clear thinking as opposed to a philosophical ideology of some kind. Against Rem Koolhaas’s argument for post-criticality I show that we are always already critical. Pragmatism’s task is to make criticism better. I end by invoking the craft ethos as articulated by Richard Sennett in his book The Craftsman (2008), as perhaps the best model of what a pragmatist architecture might look like.